Surface glass transition temperature of amorphous polymers. A new insight with SFM - Bliznyuk, V; Assender, H; Briggs, G (2002)
The surface glass transition temperature, Tg, of several amorphous polystyrene (PS) samples each with a narrow molecular weight distribution covering the range of Mn from 3 900 to 1 340 000 has been measured by force-distance measurements using a scanning force microscope (SFM). Hysteresis in the loading-unloading cycles of the force-distance curves is observed above Tg and is ascribed to viscoelasticity at the polymer surface. The hysteresis behavior for different molecular weight samples above Tg is described in terms of the contact mechanics of the tip-surface interaction, by consideration of the relative roles of bulk viscoelasticity and peeling viscoelasticity. Data on the molecular mass dependence of thick films of the surface Tg are presented, along with the dependence of Tg on film thickness for thin films, and the annealing of films with a Langmuir-Blodgett overlayer. The results are related to existing theories describing the Tg depression at lower Mn as a result of the increased free volume in the system. The change in Tg with molecular weight of PS is steeper for the surface than the bulk Fox-Flory relationship. We show that polymer chain entanglement variation rather than the end group localization on the free surface is responsible for the observed surface Tg depression effect.